Anthropometry and fitness profile, and their relationships with technical performance and perceived effort during small-sided basketball games - Clemente, F. M.; Conte, D.; Sanches, R.; Moleiro, C. F.; Gomes, M.; Lima, R. (Research in Sports Medicine, 2019)
The purpose of this study was to analyze the relationships between anthropometric (height and weight), fitness status (aerobic capacity, Yo-Yo Intermittent Recovery Test - level 1, YYIRT-L1; countermovement jump performance, CMJ) and perceived exertion (RPE) of twenty youth (under-14 and under-16) male basketball players and their technical actions (attacking balls-AB, shots-S, received balls-RB, rebounds-R, conquered balls-CB, lost balls-LB) during five small-sided games (SSGs) formats (from 1v1 to 5v5). Pearson`s product-moment correlation coefficients tested the relationships between the anthropometric and fitness variables and the technical actions and perceived exertion during SSGs. The results of this study revealed that both anthropometry and fitness variables are associated with technical performance during SSGs. However, correlations are not clear with the levels of perceived exertion reported by players. Coaches should be aware of such relationships to better design their SSGs format and implement basketball drills based on the specific players` characteristics.